ERS statement on tracheomalacia and bronchomalacia in children. Issue 3 (28th September 2019) - Wallis, Colin; Alexopoulou, Efthymia; Antón-Pacheco, Juan L.; Bhatt, Jayesh M.; Bush, Andrew; Chang, Anne B.; Charatsi, Anne-Marie; Coleman, Courtney; Depiazzi, Julie; Douros, Konstantinos; Eber, Ernst; Everard, Mark; et al.
Tracheomalacia and tracheobronchomalacia may be primary abnormalities of the large airways or associated with a wide variety of congenital and acquired conditions. The evidence on diagnosis, classification and management is scant. There is no universally accepted classification of severity. Clinical presentation includes early-onset stridor or fixed wheeze, recurrent infections, brassy cough and even near-death attacks, depending on the site and severity of the lesion. Diagnosis is usually made by flexible bronchoscopy in a free-breathing child but may also be shown by other dynamic imaging techniques such as low-contrast volume bronchography, computed tomography or magnetic resonance imaging. Lung function testing can provide supportive evidence but is not diagnostic. Management may be medical or surgical, depending on the nature and severity of the lesions, but the evidence base for any therapy is limited. While medical options that include bronchodilators, anti-muscarinic agents, mucolytics and antibiotics (as well as treatment of comorbidities and associated conditions) are used, there is currently little evidence for benefit. Chest physiotherapy is commonly prescribed, but the evidence base is poor. When symptoms are severe, surgical options include aortopexy or posterior tracheopexy, tracheal resection of short affected segments, internal stents and external airway splinting. If respiratory support is needed, continuous positive airway pressure is the most commonly used modality either via a face mask or tracheostomy. Parents of children with tracheobronchomalacia report diagnostic delays and anxieties about how to manage their child's condition, and want more information. There is a need for more research to establish an evidence base for malacia. This European Respiratory Society statement provides a review of the current literature to inform future study. This statement provides a comprehensive review of the causes, presentation, recognition and management of children with tracheobronchomalacia written by a multidisciplinary Task Force in keeping with ERS methodology http://bit.ly/2LPTQCk